Endotypes of chronic rhinitis: A cluster analysis study. Issue 4 (18th November 2018) - Meng, Yifan; Lou, Hongfei; Wang, Yang; Wang, Xiaoyan; Cao, Feifei; Wang, Kuiji; Chu, Xiaohan; Wang, Chengshuo; Zhang, Luo
Abstract: Background: Chronic rhinitis (CR) is currently regarded as a syndrome, which presents as several endotypes. The aim of this study was to identify the CR endotype clusters and investigate the inflammatory patterns associated with the different endotypes. Methods: A total of 259 CR patients and 20 control subjects were enrolled in this prospective study. Twelve clinical variables were analyzed using cluster analysis and five inflammatory variables were measured to investigate the inflammatory patterns associated with the different clusters. Results: Six endotype clusters of CR were defined in the Chinese CR patients. Patients in cluster 1 (38.6%) were diagnosed as allergic rhinitis (AR) without asthma, and in cluster 2 (13.5%) as AR with asthma, with all demonstrating positive results for local eosinophils and high levels of local and serum IgE. Similarly, patients in cluster 3 (18.6%) were diagnosed as nonallergic rhinitis with eosinophilia syndrome (NARES) without asthma and in cluster 5 (5.0%) as NARES with asthma, with all demonstrating positive results for local eosinophils, and negative results for both local and serum IgE. Patients in cluster 4 (4.6%) were diagnosed as local allergic rhinitis and showed positive results for local eosinophils and local IgE, but negative results for serum IgE, whereas patients in cluster 6 (19.7%) were diagnosed as idiopathic rhinitis because of high symptoms scores, but negative findings for local eosinophils, local IgE, and serum IgE. Conclusions: Chinese CR patients may be clustered into six endotypes with different inflammatory patterns, which may help in delivering individualized treatment. Abstract : Chinese CR patients could be clustered into six endotype clusters, including: (1) Allergic rhinitis without asthma; (2) Allergic rhinitis with asthma; (3) nonallergic rhinitis with eosinophilia syndrome (NARES) without asthma; (4) local allergic rhinitis; (5) NARES with asthma; (6) idiopathic rhinitis. Clusters 1, 2, 3 and 5 demonstrated significantly higher levels of eosinophil cationic protein and leukotriene C4 (LTC4); whereas cluster 4 demonstrated significantly higher levels of histamine and LTC4. Similarly, Cluster 6 demonstrated significantly higher levels of vasoactive intestinal peptide and substance P.